UNUSUAL CASE OF PENETRATING FISH HOOK IN LATERAL CANTHUS OF A KID - N. Krishaveni; Chhavi Gupta; A.R. Ninu; V. Prabhakaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A one year old, male, goat was presented with the history of fish hook injury on the right eye during grazing near the pond. On clinical examination, the vital parameters were normal. Ophthalmic examination of right eye revealed fish hook’s nylon with its shank at the lateral canthus. Under local anaesthesia, barbed fish hook, penetrating the palpebral conjunctiva was surgically removed after lateral canthotomy.